Increased expression of the ubiquitin – proteasome pathway in murine myotubes by proteolysis-inducing factor (PIF) is associated with activation of the transcription factor NF-κB - Whitehouse, A S (Nature Publishing Group, 2003)
Proteolysis-inducing factor (PIF), isolated from a cachexia-inducing murine tumour, has been shown to stimulate protein breakdown in C(2)C(12) myotubes. The effect was attenuated by the specific proteasome inhibitor lactacystin and there was an elevation of proteasome ‘chymotrypsin-like’ enzyme activity and expression of 20S proteasome α-subunits at concentrations of PIF between 2 and 16 nM. Higher concentrations of PIF had no effect. The action of PIF was attenuated by eicosapentaenoic acid (EPA) (50 μM). At a concentration of 4 nM, PIF induced a transient decrease in IκBα levels after 30 min incubation, while no effect was seen at 20 nM PIF. The level of IκBα, an NF-κB inhibitory protein, returned to normal after 60 min. Depletion of IκBα from the cytosol was not seen in myotubes pretreated with EPA, suggesting that the NF-κB/IκB complex was stabilised. At concentrations between 2 and 8 nM, PIF stimulated an increased nuclear migration of NF-κB, which was not seen in myotubes pretreated with EPA. The PIF-induced increase in chymotrypsin-like enzyme activity was also attenuated by the NF-κB inhibitor peptide SN50, suggesting that NF-κB may be involved in the PIF-induced increase in proteasome expression. The results further suggest that EPA may attenuate protein degradation induced by PIF, at least partly, by preventing NF-κB accumulation in the nucleus.